Studi Tentang Fenomena Anak Putus Sekolah Di SMA Negeri 2 Muara Badak Kabupaten Kutai Kartenegara - Eva Yunita; Jawatir Pardosi; Endang Herlah; Wingkolatin Wingkolatin; Warman Warman; Jamil Jamil (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This research aims to determine the study of the phenomenon of children dropping out of school at SMA Negeri 2 Muara Badak, Kutai Kartenegara Regency. This type of research is descriptive qualitative. The focus of this research is to determine the phenomenon of female students dropping out of school at SMA Negeri 2 Muara Badak and the school's efforts to deal with female students dropping out of school at SMA Negeri 2 Muara Badak. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data display, data presentation and drawing conclusions.The results of this research show that the factors causing children to drop out of school at SMA Negeri 2 Muara Badak are categorized based on internal and external factors. Low internal factors include motivation and lack of understanding of the importance of education, intelligence and learning disorders, as well as lack of discipline regarding time. Meanwhile, external factors are caused by teachers who are angry, fierce and like to curse, and there is a lack of family support to help these children overcome their problems at school.